Resistance Training and Stroke: A Critical Analysis of Different Training Programs - Bruno Bavaresco Gambassi; Hélio José Coelho-Junior; Paulo Adriano Schwingel; Fabiano de Jesus Furtado Almeida; Tânia Maria Gaspar Novais; Paula de Lourdes Lauande Oliveira; Bismarck Ascar Sauaia; Cristiane Dominice Melo; Marco Carlos Uchida; Bruno Rodrigues (Stroke Research and Treatment)
The aim of this study was to carry out a literature review on the overall benefits of resistance training (RT) after stroke and undertake a critical analysis of the resistance exercise programs surveyed (rest interval between sets and exercises, number of sets, number of repetitions, intensity, duration of training, and weekly frequency). To obtain articles for the review, we searched PubMed, Google Scholar, and Physiotherapy Evidence Database (PEDro). Inclusion criteria were considered using the PICO (population, intervention, control/comparison, and outcome variables) model. The following characteristics were recorded for all articles: type of study, author, year of publication, participants (time after stroke, sample size, and age), benefits of RT, and structured resistance exercise programs. Positive effects of training were found on anxiety status, quality of life, muscle hypertrophy, cognitive function, strength, and muscle power. Only 5 studies described the main variables of RT in detail. Lack of control of some variables of RT may negatively affect the results of this practice. The findings of the present study may further inform health and physical conditioning professionals on the importance and necessity of using the main variables in the search for benefits for individuals with stroke.